URGENSI PERLINDUNGAN DAN PENDIDIKAN ANAK DI INDONESIA: PERSPEKTIF PENDIDIKAN ISLAM - Firman - Mansir (IAIN Pontianak, 2022)
The purpose of this study was to find out about the importance of child protection and education from an Islamic perspective. The method in this study uses the method of literature study or literature study sourced from relevant library materials with a focus on research topics. The literature analyzed in this article is obtained from several national journals and several books that are in line with the problem of children's education from an Islamic perspective, then after the required data is deemed sufficient, data analysis is carried out and followed by a conclusion. This study shows that the development of children's potential can be done through an Islamic education approach. Thus, Islamic education in the future needs to focus on and contribute greatly to the protection and education of children. Not only normative with existing arguments but also needs to give a special role so that Indonesian children do not experience trauma and mental decline. This is because the growth and development of children are strongly influenced by the education factor received from an early age.Keywords: Child Protection, Child Education, Islamic Education.